Perlindungan Hak Publik dalam Vaksinasi Lansia di Puskesmas Lubuk Buaya - Nafisa Arif, Mia; Sasmita, Siska (Policy, Law and Political Research Center, 2023)
This study discusses the protection of public rights in vaccinating the elderly at the Lubuk Buaya Health Center. Empirical facts show low acceptance of vaccination among the public, especially the elderly in the city of Padang due to concerns about side effects and the halalness of the Covid-19 vaccine and family restrictions. It is difficult for the elderly to avoid the obligation to vaccinate because proof of vaccination is used as a prerequisite for processing public documents and accessing social assistance from the government, as well as for traveling out of town. Therefore, the protection of public rights for the elderly tends to be neglected because the vaccination program promoted by the government seems to be coercive for vulnerable groups such as the elderly. This study is of the Quasi Qualitative Design type with a simple research design. Data was collected through interviews with informants in charge of vaccination for the elderly (public health center) and the elderly, observing the phenomenon of elderly vaccination at the Lubuk Buaya Health Center and studying documents on records of elderly people who had and had not been vaccinated. The findings show that the protection of public rights in the vaccination of the elderly on the first principle put forward by John Rawls is contrary to the findings, but the second principle is related to the second principle because Rawls positions freedom of basic rights as the highest value followed by guarantees. opportunity for everyone.